OPTIMALISASI MEDIA DIGITAL UNTUK PENGEMBANGAN DAN PROMOSI POTENSI WISATA ALAM DESA TOYA - Zalfa, Alvin; Al Islami, Elika; Sanubari, Ilham; Adila Rahmani, Faiza; Nengah Aditya, I; Safitri, Khairunisa; Angkat Riski, Mohammad; Paniran; Tri Ardianingsih, Veronika; Ramadhani; Hijriati, Zahratul (Universitas Mataram, 2025)
Digital media-based promotional strategies are an effective means of conveying information systematically and persuasively, in order to introduce and strengthen ideas about the tourism potential of Toya Village. The selfie phenomenon that is popular among the millennial generation can increase the attractiveness of an area as a valuable tourist destination. Therefore, the promotion of natural tourism objects in Toya Village needs to be carried out massively so that the potential of Toya Village's natural wealth is increasingly widely known, which ultimately has a positive impact on improving community welfare through the tourism sector. The use of digital media in promoting Toya Village tourism plays an important role in accelerating the dissemination of information about existing tourist destinations, considering that Toya Village, which is located in Aikmel District, East Lombok Regency, has stunning natural beauty. This activity uses qualitative methods with data collection techniques through direct observation, interviews, literature studies, and visual documentation. Developing a communication strategy integrated with digital media is the right step in introducing the natural tourism potential of Toya Village to the public.